La Tragédie de l’athée de Cyril Tourneur : une vanité dramatique ? - Elodie Likhtart (Etudes Epistémè)
Cyril Tourneur’s The Atheist’s Tragedy : dramatic vanitas ? In seventeenth century Europe a macabre atmosphere permeated everyday life, and more particularly the arts. This was particularly apparent in Elizabethan and Jacobean drama, and notably in the series of revenge tragedies which was started by T. Kyd in his Spanish Tragedy (1587). In 1611, Cyril Tourneur’s The Atheist’s Tragedy seemed to bring the series to an end. Indeed, although the play apparently belongs to the genre of revenge tragedies, it diverges from that tradition in that the ghost of the murdered father forbids his son from taking revenge. In so doing Tourneur conformed to biblical moral codes but departed from the literary convention, preventing the hero of his tragedy from acting. The Atheist’s Tragedy is replete with images reminding the audience of pictures of vanitas, and so the question arises whether this play itself could be considered as a dramatic vanitas. By making numerous references to vanitas paintings in this tragedy, as well as the vanity of the main character and the inanity of the latter’s life and death, Tourneur seems to produce a new style, that of the tragedy of vacuity which renews the genre of tragedy of revenge and perhaps even replaces it.